PENGARUH KOMUNIKASI DIGITAL MELALUI TWITTER TERHADAP PERSEPSI MASYARAKAT TENTANG PERNIKAHAN DINI DI KABUPATEN TANGERANG - Fauziah, Amanda; Haryati, Erni; Arrafni, Nadya; Ishak, Salsabila; Aditya, Toddy (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to identify how digital communication using Twitter affects people’s perceptions of early marriage in Tangerang Regency. For this quantitative research, purposive sampling method was used to select a sample from a population of active Twitter users. Data were collected through in-depth interviews and questionnaires, which were then analyzed using various statistical analysis techniques. The research shows that digital communication significantly influences people’s opinions about early marriage; information shared on Twitter has the ability to change people’s opinions. This research is expected to help relevant parties create better communication strategies to address the issue of early marriage.